The impact of the funding gap on capital projects in state universities: Case of Midlands State University (Gweru) from 2012 to 2014 - Nongerayi, Fortunate (Midlands State University, 2017)
The study focuses on the funding gap on capital projects in state universities which is a case at Midlands State University. Capital projects funded from Government capital grants in this study and members of staff in the Bursary Department, Planning Section were involved in this research as respondents to questionnaires and interviews as the researcher collected primary data. This data was then presented in tables, bar graphs, line graphs and pie charts. The study results ascertained that the main factor that leads to the funding gap in state universities is fiscal instability and its impact is that it compromises the quality of infrastructure that is built at the institution; complex projects such as the storey hostels and the library are at stand still, students do not have enough residence and learning space. Economic and political conditions hinder investment in the education sector as corporate governance is compromised in appropriation of capital grants and accessing other investment internally and externally. There is need for authorities review policies to those that clearly postulate the funding of capital projects in state universities such that growth can be accelerated to the rate at which enrolment increases. The research recommended that the government, institution‟s management and policy makers should come together to make strategic plans to come up with a suitable policy.